ChemInform Abstract: Ring Expansions within the Gold‐Catalyzed Cycloisomerization of O‐Tethered 1, 6‐Enynes. Application to the Synthesis of Natural‐Product‐Like Macrocycles. Issue 38 (30th August 2013) - Simonneau, Antoine; Harrak, Youssef; Jeanne‐Julien, Louis; Lemiere, Gilles; Mouries‐Mansuy, Virginie; Goddard, Jean‐Philippe; Malacria, Max; Fensterbank, Louis
Abstract The gold‐catalyzed cycloisomerization of O‐tethered 1, 6‐enynes proceeds via a small‐sized ring expansion leading to the tricyclic compounds that contain a substituted dihydropyran moiety.